2019
DOI: 10.1515/eng-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of geodetic risk factors occurring at the construction project preparation stage

Abstract: The work contains information on the implementation of surveying works in the road construction process. The aim of the research was to identify geodetic risk factors occurring at the stage of preparation of a construction project, the presence of which can greatly disrupt the undertaking such as the road construction. The research was carried out on the basis of expert knowledge, documentation obtained from various road construction projects and the analysis of disturbances at the initial stage of works.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In infrastructure transportation projects, Kowacka et al (2019) adopted disturbance analytics for quantifying the impact of 5 risks on project success. The analysis concluded that leveling road alignments and the limited availability of GESUT data are the primary variables influencing project success.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In infrastructure transportation projects, Kowacka et al (2019) adopted disturbance analytics for quantifying the impact of 5 risks on project success. The analysis concluded that leveling road alignments and the limited availability of GESUT data are the primary variables influencing project success.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Furthermore, factors influencing the costs of building construction vary depending on different research and literature reviews [14]. Although there are numerous sets of factors influencing building construction costs in the literature, they differ depending on the location, time, and nature of the construction project being carried out [15,16]. Moreover, in practice, many influencing factors do not directly impact construction costs.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of new technologies is visible in contemporary works, including the implementation of BIM standards in the construction investment process [27], or the use of information from the "Big Data" [6]. The authors of many papers describe the implementation of the results of their research to the construction industry [9,18,19,24], cost of construction works [13,17,21,25], risk in construction [15,16,23]. One example combining the practical aspect and high research potential are the Bayesian Networks.…”
Section: Introductionmentioning
confidence: 99%